(3GdQSGdI GdfhQhRjIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HSe dGdg GdQMef GdQMje cd fRZ Hg SeJg Edi NOeg fjQhR ehdGfG GdTjN GdGejQ GdSjO CHj HcQ eMeO Hf YHO dGdg Yf GdZQV GdeVef ai GdMQha GdLGeYI ahGJM YOg ef GdShQ GdaQbGfjI s
(3BNQgG (B:s
(3Ke HYO gPG GSQGQ jMJGL Edi GdeTGagI hGddg JYGdi jeO ai HbGA GdTjN GdGejQ GdSjO JeJ GdQSGdI GdfjQhRjI hddg GdMeO hGdefg s
(3HgG fXGe GdJYbjHIs
(3NOe HgG GHf SjfG Ydi NRGfI GdSjO GdGejQ CHj HcQ eMeO Hf YHO Gddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B897s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs